# The simplified form of the expression, ( a 2 ) − 3 ( a 3 b ) 2 ( b 3 ) 4

BuyFind

### Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071
BuyFind

### Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071

#### Solutions

Chapter 1, Problem 20RE
To determine

Expert Solution

## Answer to Problem 20RE

The simplified form of the expression is, (a)0(b)14=b14 .

### Explanation of Solution

Given information:

The expression , (a2)3(a3b)2(b3)4

Formula used:

The algebraic identity:

(am)n=amn(ab)n=anbnaman=amn .

And the factorization method.

Calculation:

Consider the expression, (a2)3(a3b)2(b3)4

(a2)3(a3b)2(b3)4

Apply the identity:.. (am)n=amn .

(a2)3(a3b)2(b3)4=(a)6a6b2b12

Apply the identity:

aman=amn

(a)6a6b2b12=(a)6+6(b)14=(a)o(b)14

Here,

a0=1

(a)o(b)14=1(b)14=(b)14

The above expression can’t be simplified further.

Thus, the simplified form of the expression is . , (a)0(b)14=b14

### Have a homework question?

Subscribe to bartleby learn! Ask subject matter experts 30 homework questions each month. Plus, you’ll have access to millions of step-by-step textbook answers!